Synthesis and characterization of methylcellulose from cellulose extracted from mango seeds for use as a mortar additive - Júlia G. Vieira; Guimes Rodrigues Filho; Carla da S. Meireles; Fernanda A. C. Faria; Dayane D. Gomide; Daniel Pasquini; Sebastião F. da Cruz; Rosana M. N. de Assunção; Leila A. de C. Motta (Polímeros, 2012)
Methylcellulose was produced from the fibers of Mangifera indica L. Ubá mango seeds. MCD and MCI methylcellulose samples were made by heterogeneous methylation, using dimethyl sulfate and iodomethane as alkylating agents, respectively. The materials produced were characterized for their thermal properties (DSC and TGA), crystallinity (XRD) and Degree of Substitution (DS) in the chemical route. The cellulose derivatives were employed as mortar additive in order to improve mortar workability and adhesion to the substrate. These properties were evaluated by means of the consistency index (CI) and bond tensile strength (TS) tests. The methylcellulose (MCD and MCI) samples had CI increased by 27.75 and 71.54% and TS increased by 23.33 and 29.78%, respectively, in comparison to the reference sample. Therefore, the polymers can be used to produce adhesive mortars.